PENGARUH EXPECTED RETURN TERHADAP PENILAIAN SAHAM DAN RISK SEBAGAI VARIABEL MODERASI (Studi Pada Perusahaan Go Public) - Tri Rinawati; Aprih Santoso (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2019)
Achieving the end of 2018, the domestic capital market has the highest number of publicly traded companies in Asia. In addition to the increasing number of issuers, the number of investors continues to grow in line with confidence in economic growth in Indonesia. At present there are 1.6 million capital market investors. PT Indonesian Central Securities Depository (KSEI) recorded the number of investors in the capital market as of December 2018 reaching 1,606,481, an increase of 43 percent since the end of 2017.The purpose of this study was to determine the effect of Expected Return and Risk on the Appraisal of Stock Companies Going Public in 2015 - 2019 and to determine the stock valuation model in moderating the influence of Expected Return and Risk on Stock Appraisal on Stock Appraisal of Go Public Companies in 2015 - 2019.The type of data used is secondary data in the form of annual financial statements of publicly listed companies listed on the Indonesia Stock Exchange. The population of this study is the company Go Public Manufacturing Sector (Consumer Goods Sector) Food and Beverage sub sector totaling 18 issuers. The sampling technique is done by using a saturated sample, which is a sample using the entire population, in this case totaling 18 issuers. Data analysis techniques used were descriptive statistical tests, classic assumption tests, multiple linear regression tests, moderating variable tests and model feasibility tests.Based on the results of the research test it was concluded that there was no significant negative effect between Expected Return on Stock Valuation. Variation of the Expected Return variable used in the model is able to explain variations in the Stock Valuation variable, while the rest is influenced or explained by other variables not included in this research model.